2016
DOI: 10.1002/mds.26629
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar dysfunction in essential tremor

Abstract: The simplest explanation for the present results is that the cerebellum itself, including the Purkinje cells, is involved in essential tremor, which may reflect a primary pathogenic lesion or secondary compensatory physiological phenomenon to an original pathogenic lesion elsewhere. © 2016 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 27 publications
(48 reference statements)
2
15
1
Order By: Relevance
“…The increased volume of cerebellar GM was associated positively with longer disease duration and higher TRS scores, which also indicated a potential compensatory mechanism. Some previous pathological and physiological studies ( 54 , 55 ) reported the compensatory mechanism of cerebellum in ET. Further clinical studies can focus on it.…”
Section: Discussionmentioning
confidence: 93%
“…The increased volume of cerebellar GM was associated positively with longer disease duration and higher TRS scores, which also indicated a potential compensatory mechanism. Some previous pathological and physiological studies ( 54 , 55 ) reported the compensatory mechanism of cerebellum in ET. Further clinical studies can focus on it.…”
Section: Discussionmentioning
confidence: 93%
“…However, two previous CBI studies have reported conflicting outcomes. Hanajima and colleagues found CBI to be significantly reduced compared to healthy controls and therefore proposed involvement of the cerebellar efferent tract in ET . In contrast, Pinto and colleagues showed normal CBI in younger, more severely affected individuals.…”
Section: Effects Of Noninvasive Cerebellar Stimulation In Diseases Afmentioning
confidence: 99%
“…The spirals of ET patients with low severity (mean = 1.4) were judged as NC, whereas the severity of ET patients mistaken for CD (mean = 2.6) was almost the same as the total ET severity (mean = 2.3). We consider the low sensitivity of ET for the following reasons: (1) slight tremors in NCs, including physiologic or senile tremor may generally be difficult to differentiate from mild ET [21], and (2) the pathophysiology of ET contains elements of cerebellar dysfunctions [22]. These problems might be solved by learning more spirals and using patients' age as a parameter in the application.…”
Section: Ai For Tremor Diagnosismentioning
confidence: 99%